Malaria Risk Factors and Mapping in Amfoang Barat Daya-Kupang Nusa Tenggara Timur - Dwita Anastasia Deo; Mahardika Agus Wijayanti; Elsa Herdiana Murhandarwati (Tropical Medicine Journal, 2012)
Introduction: Amfoang District is one of malaria-endemic areas in East Nusa Tenggara Province. The areas are adjacent to the shore at the lowland and adjacent to the forest at the highland respectively. Residential areas are surrounded by forest, shrubs, field, streams and pools of water. Most population work as farmers, have low education levels and do not use mosquito bed netObjectives: This study aims to investigate the factors that influence the incidence of malaria risk and determine the pattern of clustering of cases in the Amfoang Barat Daya, District of Kupang, Nusa Tenggara Timur.Methods: Mass blood surveys were conducted to investigate malaria cases in three villages in October 2011, January 2012 and April 2012. The 3,515 blood samples were collected for thick blood film. Riskfactors were identified through questionares and OR were calculated. Significance was assumed at p <0.05. Coordinates were taken from residence of patients by GPS and analyzed with Purely Spatial Bernaullymodel to investigate any cluster of malaria cases. River with potentials breeding place was buffered 1km by ArcGis to determine whether malaria cases were in the mosquito fly distance areas.Results: Dry land farmer, education, malaria symptomatic, habitual of sleep outdoors, farming and fishing (06.00pm-06.00 am), outdoors gathering (06.00pm-06.00 am), wooden wall, mosquito wire, ventilation, plafond, animal shelter distance, breeding place and climate were insignificant for prevalence of malaria. Bed nets and breeding place were significant for prevalence of malaria. Potential of malaria vectors (An. barbirostris and An. sundaicus) were found in lowlands but was not found in highlands. Bed nets is protective factor from incidence of malaria. One primer most likely cluster and 3 secondary clusters were insignificant.Conclusion : Lowland has risk from malaria. The use of bed nets during 06.00pm – 06.00am is as protective factor for malaria OR 0.1.Keyword:Amfoang Barat Daya, risk factormalaria, thick blood smear, Anopheles sp., bed nets,mapping